The Phototextual Emergence of Hysteria: From the Iconographie Photographique de la Salpêtrière to J. M. Coetzee’s Slow Man - Gilburt, Iona (Kronos: Southern African Histories, 2021)
This article seeks to examine the emergence of the image of hysteria that originated at the Salpêtrière Hospital in Paris in the late nineteenth century and has since been transferred across new generations of phototexts through ekphrasis. It is first shown how this stereotypically feminine and sexualised image was initiated by the medical tome Iconographie Photographique de la Salpêtrière – an effect that belies the physicians’ original intentions – and is then taken up in the public imagination by the surrealists André Breton and Louis Aragon before emerging in Georges Didi-Huberman’s 1982 critical text Invention of Hysteria. Didi-Huberman’s monograph offers insight into how persistent this image becomes, even taking shape in discourses that attempt to undermine it. Didi-Huberman furthermore highlights how developments in photographic technology have contributed to the shaping of hysteria. Finally, this article considers how the figure of the hysteric appears in J. M. Coetzee’s 2005 novel Slow Man in the character of Marianna. The manner in which she is depicted presents an ekphrasis that can be matched to the vision of hysteria that began with the Iconographie Photographique de la Salpêtrière, thereby showing how this histrionic and gender-stereotyped iteration of hysteria from the nineteenth century remains a readily accessible mode of expression.